Applied process design for chemical and petrochemical plants. Volume 1, Emphasizes how to apply techniques of process design and interpret results into mechanical equipment details - Ludwig, Ernest E. (Houston : Gulf Pub. Co., 1995)
This expanded edition introduces new design methods and is packed with examples, design charts, tables, and performance diagrams to add to the practical understanding of how selected equipment can be expected to perform in the process situation. A major addition is the comprehensive chapter on process safety design considerations, ranging from new devices and components to updated venting requirements for low-pressure storage tanks to the latest NFPA methods for sizing rupture disks and bursting panels, and more. *Completely revised and updated throughout *The definative guide for process engineers and designers *Covers a complete range of basic day-to-day operation topics.
Process planning, scheduling, flowsheet design -- Fluid flow -- Pumping of liquids -- Mechanical separations -- Mixing of liquids -- Ejectors and mechanical vacuum systems -- Process safety and pressure-relieving devices -- Appendix of conversion factors.
Includes bibliographical references and indexes.
Keywords: Chemical plants -- Equipment and supplies; Petroleum industry and trade -- Equipment and supplies; Electronic books